IMPROVING THE TEACHING METHODOLOGY OF INFORMATICS AND INFORMATION TECHNOLOGIES IN PRIMARY CLASSES UNDER DIGITAL CONDITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the attention to digital education in our country and special attention to the requirements for teaching computer science from elementary grades and the educational programs, new content and new textbooks related to it, the necessary methodological support Opinions about the development of manuals are given. In order to improve informatics and IT science in elementary grades, it is appropriate to compare the knowledge of children in traditional previous education with the new improved methodology, and the effectiveness of teaching in it indicates how correctly this methodology was chosen. This can be seen from the introduced changes and from the children's increased knowledge of informatics, knowledge indicators.